Pengaruh Kreativitas Iklan, Unsur Humor, Dan Kualitas Pesan Iklan Terhadap Efektivitas Iklan Youtube Gojek Versi Gojek Paling Hemat - Amjad, Muhammad Silmy; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine and analyze the effect of advertising creativity, , elements of humor, and the quality of advertising message on the effectiveness of youtube advertising Gojek the most economical version of Gojek. This research uses case studies on active students of the Manajement Study Program, Faculty of Economics and Business, Islamic University of Malang who were selected by purposive sampling. Determination of the number of samples using the Malholtra formula and the results obtained were 75 respondents. Data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Hypothesis Test (F test and t test), and Determination Coefficient Test (Adjusted R2). Process analysis using SPSS. The results of the study state that advertising creativity,elements of humor, an the quality of advertising messages simultaneously influence advertising effectiveness and partially advertising creativity, elements of humor, and quality of advertising messages have a positive and significant influence on advertising effectiveness. Keywords: Advertising Creativity, Elements Of Humor, Quality Of Advertising Messages, Advertising Effectiveness.